Effects of prenatal and postnatal Tocotrienol-rich fraction supplementation on cognitive function development in F1 male rats - Nagapan, Gowri (2014)
The intake of specific nutrients during the critical period in early life influence cognitive and behavioural development profoundly. Antioxidants such as vitamin E have been postulated to be pivotal in this process, as vitamin E is able to protect the growing brain from oxidative stress. Currently, tocotrienols are gaining much attention due to their potent antioxidant and neuroprotective properties. It is thus compelling to look at the effects of prenatal and early postnatal tocotrienols supplementation, on cognition and behavioural development among offspring of individual supplemented with tocotrienols. Therefore, this study was aimed to investigate potential prenatal and early postnatal influence of Tocotrienol-Rich Fraction (TRF) supplementation on vitamin E content in plasma and tissues; fatty acid profiles in brain and cognitive function developments in male F1 rats. Eight-week-old adult female Sprague Dawley (SD) rats (F0 generation) were randomly assigned into five groups of two animals each. The animals were fed either with the base diet as control (CTRL), base diet plus vehicle (VHCL), base diet plus docosahexanoic acid (DHA), base diet plus Tocotrienol-Rich fraction (TRF), and base diet plus both docosahexaenoic acid, and tocotrienol rich fraction (DTRF) diets for two weeks prior to mating. The F0 females were maintained on their respective treatment diets throughout the gestation and lactation periods. Pups (F1 generation) derived from these dams were raised with their dams from birth till four weeks post natal. The male pups were weaned at eight weeks postnatal, after which they were grouped into five groups of ten animals each, and fed with the same diets as their dams for another eight weeks. Learning and behavioural experiments were conducted only in F1 male rats using the Morris water maze (MWM).The vitamin E content of the diets, plasma and tissues of the male F1 rats were determined using standard extraction and High Performance Liquid Chromatography procedures. Results showed that vitamin E content, α-tocopherol and α-tocotrienol were found increased in the plasma, brain and liver of the TRF and DTRF groups than CTRL group (P<0.05). δ-Tocotrienol was found increased in the adipose of TRF and DTRF groups than CTRL group (P<0.05). Results also showed that the DHA content and total n-3 PUFA in the brain of the DHA and DTRF groups were significantly higher and their n-3: n-6 ratio significantly lower than CTRL group (P<0.05). TRF supplementation had no detectable effects on the PUFA profiles of the brain tissues of male F1 rats. Animals supplemented with either DHA and/or TRF such as DHA, TRF and DTRF groups demonstrated better spatial learning and re-learning ability compared to the CTRL animals (P<0.05). The cognitive parameters of TRF supplemented animals from the current study were comparable to that of the DHA group which was a positive control for this experiment. In conclusion, the current study demonstrated that prenatal and postnatal intake of TRF increases the α-tocotrienol level in the progeny’s brain. This results in better behavioural performance and cognitive function development in the F1 progeny.